Performance Index and Economic Efficiency of SASSO C44 Broilers Fed Diets Containing Graded Levels of Dried Blood-Rumen Content Mixture to Replace Roasted Soybean Meal - Melkamu Bezabih Yitbarek; Birhan Tamir; Ashenafi Mengistu (European Scientific Journal, ESJ, 2018)
This experiment was carried out to evaluate performance index and economic efficiency of broiler chicks fed diets containing dried blood rumen content mixtures (DBRCM) as a replacement for roasted soybean meal (RSBM). A total of 225 unsexed day-old broiler chicks (SASSO C44) were randomly allocated to five dietary treatments in a completely randomized design. Each treatment was replicated thrice with 15 birds per replicate. The experimental diets were formulated to contain 100% RSBM+0%DBRCM (T1), 80%RSBM+ 20% DBRCM (T2), 60% RSBM + 40% DBRCM (T3), 40% RSBM + 60% DBRCM(T4) and 20% RSBM+ 80% DBRCM (T5) based on a control ration contained 30% roasted soybean meal. The result showed that there was no statistical difference (P≥0.05) in performance index during the experimental period. The mean mortality was not influenced (P≥0.05) across the treatment groups. Birds fed T1 had the highest (P<0.05) and T5 the lowest (P<0.05) feed cost per kilogram feed. Feed cost per unit gain (Kg) was the highest (P<0.05) for T1 and the lowest (P<0.05) for T4 and T5. Total feed cost of the birds fed T1 was higher than those of the birds fed T5 diet. The highest (P<0.05) economic efficiency was observed for birds fed on T4 and T5. Based on this result, it could be concluded that 80% DBRCM can replace roasted soybean meal to achieve the highest economic efficiency, without affecting the performance index of broiler chicken.